2017
DOI: 10.1534/genetics.116.195594
|View full text |Cite
|
Sign up to set email alerts
|

Trends in DNA Methylation with Age Replicate Across Diverse Human Populations

Abstract: Aging is associated with widespread changes in genome-wide patterns of DNA methylation. Thousands of CpG sites whose tissue-specific methylation levels are strongly correlated with chronological age have been previously identified. However, the majority of these studies have focused primarily on cosmopolitan populations living in the developed world; it is not known if age-related patterns of DNA methylation at these loci are similar across a broad range of human genetic and ecological diversity. We investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 81 publications
(138 reference statements)
6
49
0
Order By: Relevance
“…This work is the first demonstration, to our knowledge, of a functional role for Elovl2 in regulating age‐associated phenotypes in the retina. Methylation of the promoter region of ELOVL2 is well‐established as a robust prognostic biomarker of human aging (Garagnani, ; Gopalan, ), but whether ELOVL2 activity contributes to aging phenotypes had not yet been documented. In this work, we demonstrated that the age‐related methylation of regulatory regions of Elovl2 occurs in the rodent retina and results in age‐related decreases in the expression of Elovl2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is the first demonstration, to our knowledge, of a functional role for Elovl2 in regulating age‐associated phenotypes in the retina. Methylation of the promoter region of ELOVL2 is well‐established as a robust prognostic biomarker of human aging (Garagnani, ; Gopalan, ), but whether ELOVL2 activity contributes to aging phenotypes had not yet been documented. In this work, we demonstrated that the age‐related methylation of regulatory regions of Elovl2 occurs in the rodent retina and results in age‐related decreases in the expression of Elovl2 .…”
Section: Discussionmentioning
confidence: 99%
“…This work is the first demonstration, to our knowledge, of a functional role for Elovl2 in regulating age-associated phenotypes in the retina. Methylation of the promoter region of ELOVL2 is wellestablished as a robust prognostic biomarker of human aging (Garagnani, 2012;Gopalan, 2017), but whether ELOVL2 activity contributes to aging phenotypes had not yet been documented. F I G U R E 3 Elovl2 C234W mice show a loss of ELOVL2 enzymatic activity.…”
Section: Elovl2 As a Critical Regulator Of Molecular Aging In The Rmentioning
confidence: 99%
“…A primary goal of the current analyses was to test whether markers of children's growth and energetic condition and their experiences of family life that could influence their psychosocial stress and health were correlated with higher EAA in a small‐scale society setting, building from recent related research in similar contexts on adults (Fagny et al, ; Gopalan et al, ; Horvath et al, ). A small but growing number of studies of epigenetic aging in children have attempted to explore the developmental origins of EAA given its implications for mortality and morbidity across the life course (Brody, Yu, et al, ; Davis et al, ; Moore et al, ; Simpkin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A small but growing number of studies of epigenetic aging in children have attempted to explore the developmental origins of EAA given its implications for mortality and morbidity across the life course (Brody, Yu, et al, ; Davis et al, ; Moore et al, ; Simpkin et al, ). However, the vast majority of these studies have been conducted with industrialized populations in societies in which under‐nutrition, energy shortfalls, and/or infectious disease stressors are typically absent or minimal (Fagny et al, ; Gopalan et al, ; Horvath et al, ; Ryan et al, ). Because those conditions diverge from the developmental experiences of many global populations as well as the conditions under which human biology evolved (Gurven, ; Horvath et al, ; Lozano et al, ), it is important to understand the role of concurrent experiences of energetic trade‐offs and psychosocial stressors in relationship to EAA.…”
Section: Discussionmentioning
confidence: 99%
“…Gopalan et al . [72] found patterns of methylation in African hunter-gatherers (Baka CAHG and San) that could be useful for inferring age, particularly in geographic regions where age is often unknown. Taken together, these epigenomic studies highlight how genetic variation and environment can influence methylation patterns, which in turn can influence adaptive trait variation.…”
Section: Adaptation In Sub-saharan Africamentioning
confidence: 99%